A New Species of the Durophagous Mosasaurid Carinodens from the Late Maastrichtian Phosphates of Morocco and Implications for Maastrichtian Mosasaurid Diversity - Nicholas R. Longrich; Xabier Pereda-Suberbiola; Nour-Eddine Jalil; Nathalie Bardet (Diversity)
Late Cretaceous marine ecosystems saw a major adaptive radiation of mosasaurids, which evolved highly disparate jaw and tooth morphologies to feed on different prey. A striking pattern seen in mosasaurids was a high diversity of durophagous forms. Durophagy likely evolved several times independently in the mosasaurine genera Globidens, Prognathodon, and Carinodens. Carinodens is unusual in having low, rectangular, laterally compressed teeth. The genus is known from around the world, with the species Carinodens minalmamar and C. belgicus previously reported from the Maastrichtian Phosphates of Morocco. Here, we report a new species of Carinodens, C. acrodon, from the same Maastrichtian Phosphates. It is characterized by teeth with tall crowns, triangular apices, and broad bases. Many of the diagnostic features of this species appear to be plesiomorphies, suggesting the persistence of a primitive species of Carinodens into the latest Maastrichtian alongside the more derived C. minalmamar and C. belgicus. The new species contributes to an emerging pattern of mosasaurid hyperdiversity in the late Maastrichtian of Morocco. A revised faunal list, including stratigraphic range extensions of Khinjaria and Stelladens into the latest Maastrichtian of upper Couche III of the Phosphates of Morocco, suggests at least 16 species of mosasauroid coexisted here.